Evaluation of current coal burst control techniques and development of a coal burst management framework. (November 2018) - Wei, Chunchen; Zhang, Chengguo; Canbulat, Ismet; Cao, Anye; Dou, Linming
Abstract: Coal burst has been increasingly attracting attention in Australian coal mines recently as they go deeper. Coal burst is well known for its catastrophic destruction, complex mechanisms and difficulty of control in the mining industry. This paper summarises the control measures used globally for this dynamic failure, and shows how to develop site specific control management plans. Firstly, relevant terminology used in dynamic rock failure events in the international underground mining industry is discussed. Preventative controls and mitigating controls are then presented and discussed. Current coal burst controls include general management strategy, mine design, preconditioning and destressing as risk mitigation, and ground support strategies. Optimum layout methods, mitigating strategies, including latest ground support techniques and destressing techniques, are reviewed in this paper. A framework of coal burst management is then proposed, including three critical stages: identification of coal burst profile, development of a management plan and management of coal burst.